KAJIAN PERTUNASAN EMPAT KULTIVAR MANGGA (MANGIFERA INDICA L.) YANG TELAH MENGALAMI PEMANGKASAN AWAL DAN PEMUPUKAN KNO3 - Rugayah, Rugayah (JURNAL AGROTROPIKA, 2009)
The research was conducted to study shoot-growth pattern on four cultivars of mango ( Arumanis, Gedong, Indramayu, Manalagi) that was early pruning and application of KNO3.The treatment was arranged factorially (2x5) in a randomized block design with four replication. The first factor were posision of pruning: on the first flush (P1) and the second flush (P2) and the second factors were concentration of KNO3 (0, 2, 4, 6, 8) g/l. Observations were made in two periods (flush I and flush II). The observation on the first period has been written in Satek-II Proceeding?s, 2008 but the results in the second period showed that:. 1) Pruning the second flush position further increase (the number of leaves per shoot, shoot length, and the total number of leaves per plant) on cv Arumanis, increasing the total number of leaves per plant on Manalagi cultivars, and increase the number of leaves per shoot at Indramayu cultivars than in the first flush position. 2) The application of KNO 3 on Manalagi cultivars reduced the total number of leaves, but the cultivar of Indramayu with concentration of 2 g / l to increase the length of shoots, and on two other cultivars (Arumanis and Gedong) had no effect. 3) There is no interaction between pruning and application of KNO 3 on all cultivars tested.Key words: Cultivars of mango: Manalagi, Gedong, Arumanis, Indramayu, Pruning, KNO3, Flush